Analysis of Mompreneur Entrepreneurial Behavior: A Case Study of Home Baking Entrepreneurs - Inanna Inanna; Mustari Mustari; Tuti Supatminingsih; Muhammad Hasan (Dinamika Pendidikan, 2023)
This study aimed to determine the driving factors for the emergence of entrepreneurial behavior of mompreneurs and entrepreneurial behavior applied by mompreneurs in home baking businesses in Kalibone village, Pangkep Regency. This study used a qualitative approach method. Data analysis was carried out through the stages of data collection, data reduction, data presentation and drawing conclusions. Testing the validity of the data was carried out by comparing the findings from different data sources. The informants in this study were six mompreneurs who have home baking businesses. The results showed that the driving factors for the emergence of entrepreneurial behavior were independence, namely the ability of mompreneurs to rely on themselves by opening new business fields and not relying on others, then coercion, namely the mompreneur had no other choice but to do entrepreneurship, and capital ownership, namely the existence of assets owned by the mompreneur in the form of money, or other property rights that were used as capital in starting a business. Entrepreneurial behaviors that emerged from mompreneurs were independent, proactive, competitive, innovative, and courage to face the challenges that occurred in running their business.